Analyzing the Language Style of Generation Z Teenagers in Their Instagram Posts - Yasminar Amaerita Telaumbanua; Nicky Elvin Crsitin Zendrato; Benedicta Trisanta Nazara; Eldin Curtiel Harefa; Afridayanti Harefa (JELITA, 2024)
This research aimed to (i) analyze the predominant language styles used by Generation Z teenagers in their Instagram posts and (ii) identify the factors influencing these language styles. This qualitative research employed a constructivism approach, utilizing interviews and document analysis as instruments for data collection. The research participants comprised 10 Generation Z teenagers, and the study focused on their Instagram posts from January 2023 to June 2024. Data were analyzed using condensation, display, and conclusion drawing/verifying stages. The findings indicated that Generation Z teenagers predominantly use casual language styles in their Instagram posts, characterized by the frequent use of slang, colloquial language, abbreviations, and informal greetings and farewells. Several factors influencing these language styles were identified, including technological affordances, social factors, and linguistic trends. This research contributes to the theoretical understanding of language evolution in digital contexts, particularly among digital natives, offering insights into how social media platforms like Instagram influence language use and the emergence of new linguistic trends within specific generational cohorts.